Digital Shift: Optimizing Sika LMS in Digital Communication Technology Education to Encourage Students' Discipline and Productivity in Reaching Goals - Wulan, Rayung; Sunarto, Sunarto; Kholil, Kholil (Universitas Pendidikan Ganesha, 2025)
The shift towards digitalization in higher education learning is marked by developments in communication technology and the transition from computer-mediated communication (CMC) to digital technology-based learning. This change has had a significant impact on improving student achievement and timely graduation. The study aims to analyze and explain the variables that are problems in the digital shift in digital technology-based learning patterns in SIKA LMS media and efforts to encourage Unindra informatics engineering students to achieve timely graduation by adopting the CMC (Computer Mediated Communication) theory. The method uses a comparative analysis approach by comparing and contrasting data based on categories and variables. Data collection involves interviews with students, blended learning managers, and lecturers. The interview results were processed with Computer-Assisted Qualitative Data Analysis Software (CAQDAS), Maxqda Analytics application, by identifying metadata, tabulation factor collection, coding system, and frequency of relations. The results of this study indicate that the Code model tendency obtained by a digital shift in the discipline of using digital technology has a very significant role in the change of learning patterns to achieve student graduation productivity; these results are input for higher education institutions in the current digitalization.